Primary pneumococcal peritonitis can be the first presentation of a familial complement factor I deficiency1. (24th July 2020) - Ugrinovic, S.; Firth, H.; Kavanagh, D.; Gouliouris, T.; Gurugama, P.; Baxendale, H.; Lachmann, P. J.; Kumararatne, D.; Gkrania‐Klotsas, E.
Summary: Primary pneumococcal peritonitis is a rare infection that has been described in women but has not been previously linked with immunodeficiency. The complement system plays a central role in immune defence against Streptococcus pneumoniae and, in order to evade complement attack, pneumococci have evolved a large number of mechanisms that limit complement‐mediated opsonization and subsequent phagocytosis. We investigated an apparently immunocompetent woman with primary pneumococcal peritonitis and identified a family with deficiency for complement factor I. Primary pneumococcal peritonitis should be considered a possible primary immunodeficiency presentation. Abstract : We describe a case of primary pneumococcal peritonitis which uncovered a family with compound heterozygous deficiency for complement factor I. Primary pneumococcal peritonitis has been described in women but has not been previously linked with complement disorders. We propose that unexplained pneumococcal peritonitis should be considered a "red flag" for primary immunodeficiency.